The Beyond Intention: the Roles Perceived Sharia Compliance in Explaining Actual Use of Islamic P2P Financing Among Muslim Students - M.Khairul Anwari; Nur Afifah; Mustaruddin Mustaruddin; Titik Rosnani (Jurnal Riset Akuntansi, 2026)
The rapid growth of Islamic financial technology has created new opportunities for expanding financial inclusion among young Muslims. However, limited evidence exists regarding the factors that drive actual usage of Islamic peer-to-peer (P2P) financing, particularly among university students. This study examines the effects of Islamic financial literacy dimensions (financial knowledge, financial behavior, and financial attitude) and trust on actual use behaviour of Islamic P2P financing through the mediating role of intention and the moderating role of perceived sharia compliance. A quantitative survey was conducted among 153 Muslim students in Pontianak, Indonesia, and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that financial behaviour and trust significantly influence intention, whereas financial knowledge and financial attitude do not. Furthermore, perceived sharia compliance has a significant direct effect on actual use behavior. Surprisingly, intention does not significantly affect actual use behaviour, indicating the existence of an intention–behaviour gap. In addition, perceived sharia compliance fails to strengthen the relationship between intention and actual use behaviour. These findings extend TPB, TAM, and Sharia Compliance Theory by demonstrating that actual usage of Islamic fintech is driven more by trust and perceived sharia compliance than by intention alone.